Inductance estimation method for linear switched reluctance machines considering iron losses. Issue 3 (1st March 2016) - Wang, Qianlong; Chen, Hao; Xu, Tong; Yuan, Jinxia; Wang, Jiewei; Abbas, Saleem
Abstract : The voltage pulse injection method is widely used at the starting and low‐speed sensorless operation of the rotary switched reluctance machine (SRM) and the linear SRM (LSRM). The conventional methods for the inductance estimation in voltage pulse injection, the current peak value method, and the current slope difference method have a limitation that the iron losses in the controlled SRMs/LSRMs should be negligible. In this study, a new inductance estimation method in the voltage pulse injection is proposed considering the iron losses. Assuming that the iron‐loss currents in the energising and de‐energising intervals are almost equal, the inductance estimations in the two intervals are conducted, respectively, and the actual inductance values without the influence of the iron losses can be obtained by a special operation of the two calculated inductance values. Take a designed LSRM as a test object, the results of the proposed method coincide well with the actual values as compared with the conventional methods. The novel inductance estimation can be utilised in the SRMs/LSRMs without the limitation of the iron losses, and then it can further improve the accuracy of the sensorless control in the voltage pulse injection method.